IMPLIKASI COVID 19 TERHADAP PEMBELAJARAN DI PERGURUAN TINGGI - Bustomi, Ahmad (IAIIG Cilacap, 2020)
This Research was condusted because of the emergence of a virus namely corona virus disease 19 (called Covid 19) which is endemic throughout the world. The ministry of education in Indonesia which calls for education to be carrid out through cyberspace to reduce contagion of Covid 19. Therefore this research is important because the movement of the learning process is due to to the Covid 19 epidemic that engulfs the world from face to face into face to distance which usually becomes very interesting. This research focuses on the description of learning in tertiary institutions which should change most of the learning process from face to face into face to distance.This research is a field reserach with a qualitative approach. The data colleection techniques using trianggulation (combination), the data analysis caracterized induktive/qualitative, and the result of qualitatif research more emphasis on meanings rather than generalization. The subject of this research are Dr. Rina Khairani Pancaningrum LLM. as a lecturer of Mataram University, Abdul Basit Atamimi. M.Hum. as a lecturer of Muhammadiyah University of Cirebon, Yusuf hasan Baharudin, M.Pd.I. as a lecturer of Nahdlatul Ulama Al Ghazali University in Cilacap, Mochammad Afroni, M.Pd.I as a lecturer of STIT in Pemalang dan Aminul Qodat, M.Pd. as a lecturer STIT Al Mubarok in Lampung Tengah. The method of collecttion data uses observation, interview and documentation study. The data analisys techniques in this resarch use miles and huberman theory, namely data reduction, data display and conclusion drawing/verification (conclution).The result of this research showe that: Firstly, The implications of Covid 19 establish the learning move from face to face learning in the classroom change into on the virtual world, whether face to face or not face to face. Secondly, the learning movement through virtual world presents new problems, namely the unpereparedness of lecturers, the minimum of facilities, high cost and ineffective learning.